(untitled) - FAO (Rome, Italy, 1984)
This book provides information of a technical and economic nature on the processes and equipment for the parboiling of rice, based on direct experience in the design, etablishment, technical operation and management of commercial parboiling and milling plant
Keywords: rice - processing,rice, parboiled